Change in the contribution of spring snow cover and remote oceans to summer air temperature anomaly over Northeast China around 1990. Issue 2 (30th January 2014) - Wu, Renguang; Zhao, Ping; Liu, Ge
Abstract Sea surface temperature (SST), snow cover, and soil moisture anomalies are factors for climate variability over land regions. The present study found that the relationship between in situ spring snow cover and Northeast China summer surface temperature variations is not steady. It is significant during mid‐1970s through late 1980s but weak during the 1990s and 2000s. This interdecadal change in the spring snow cover‐summer temperature relationship is found to relate to the effects of SST anomalies in the tropical Indian Ocean and western Pacific regions during the recent decades. These SST anomalies induce a meridional circulation pattern along the East Asian coast. The remote SST forcing‐induced circulation and precipitation anomalies overcome local snow cover‐induced soil moisture anomalies and thus disrupt the spring snow cover‐summer temperature connection during the recent decades. The present study indicated that both the North Atlantic SST anomaly pattern and local spring snow cover anomalies contribute to Northeast China summer temperature variations during mid‐1970s through late 1980s. During the 1990s and 2000s, the influence of the North Atlantic SST anomalies is weakened, and the SST anomaly in the tropical Indo‐western Pacific region is a major player in Northeast China summer temperature variations.